Analisis Pola Faktor Penyebab Balita Stunting Pada Dinas Kesehatan Kota Bekasi Menggunakan Algoritma FP-Growth - Khoirunnisaa, Nabiilah; Priatna, wowon; -, Rasim; Warta, Joni (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2024)
Stunting is a common long-term nutritional problem among children under five, especially in developing countries, including Indonesia. Recently, the term stunting has become a popular topic of discussion while diverting attention from the problems of malnutrition and obesity. This study aims to determine the results of the formation of rules or association rules in determining the causal factors that most affect stunting in toddlers at the Bekasi City Health Office. The method that will be used in this research is the FP-Growth Algorithm. With the application of the FP-Growth Algorithm, accurate results can be obtained in determining the rules for determining the causal factors that most affect stunting in toddlers. The dataset has 4575 data and will be evaluated using the lift ratio. This research produces 26 rules, the best of which are Not Getting Exclusive Breastfeeding, Thinness, and Malnutrition, with a minimum support value of 0.5, a confidence value of 0.6, and a lift ratio of 1.17. Thus, applying the FP-Growth Algorithm in this study is effective because it achieves a lift ratio value of more than 1.